Nordic Security and Defence Cooperation: Differentiated Integration in Uncertain Times - Bengtsson, Rikard (2020)
A decade ago, Nordic cooperation on security and defence matters gained momentum, having been largely absent from the map of Nordic cooperation during the Cold War and its aftermath. This article analyses developments along three dimensions of Nordic cooperation: military defence (focusing on the Nordic Defence Cooperation), civil security (in the form of the ‘Haga’ process), and political cooperation (through the implementation of the Stoltenberg report). Three observations stand out as a result: First, that the three dimensions are intimately related against the background of a common Nordic conceptualization of security; second, that there is simultaneously variation in significant respects (such as driving forces, scope, and degree of institutionalization); and third, that Nordic security and defence cooperation has developed in the context of European and transatlantic security dynamics and cooperation. The second part of the analysis seeks to interpret this picture from the analytical perspective of differentiated integration. The article ends with a set of reflections on the future of Nordic security and defence cooperation in light of the Coronavirus pandemic.